Religious Attitude dengan Perilaku Prososial pada Relawan PMI Kota Surabaya: Indonesia - Andari Nur Rahmawati; Rizma Fithri (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2020)
Prosocial behavior in individuals is one of the social competencies that volunteers must possess to encourage positive social interaction. Prosocial behavior by volunteers reflects a commendable social act. One of the factors that influence prosocial behavior is religion. The purpose of this study was to determine the relationship between religious attitudes with prosocial behavior in KSR PMI Surabaya City. This research is correlational in quantitative research. This research uses the scale of religious attitude and prosocial behavior scale. The number of subjects in the study N = 80 of the total population of 400 members of the KSR PMI Surabaya City through a purposive sampling technique. Hypothesis testing in this study uses product-moment with the help of SPSS. The result of this study indicates there is a relationship between religious attitudes with prosocial behavior in KSR PMI Surabaya City. (r = 0.653, p=0.000 < 0.05). This hypothesis in this study accepted that religious attitude correlates with prosocial behavior in KSR PMI Surabaya City. It means that the higher the religious attitude in KSR PMI Surabaya City, the higher the prosocial behavior. This research carried out to give an idea of the importance of having prosocial behavior not only for volunteers but for all individuals, considering that individuals are social creatures